The role of professional organisations in nursing advancement - R. Bergman (AOSIS, 1983)
Some thoughts are pre sented on the role of professional organisations in nursing advancement and the development of a model for nurses' associations in setting objectives, priorities and activities relative to their roles is shared with the reader.